Cpeb1 expression is post‐transcriptionally regulated by AUF1, CPEB1, and microRNAs. Issue 1 (8th November 2021) - Oe, Souichi; Hayashi, Shinichi; Tanaka, Susumu; Koike, Taro; Hirahara, Yukie; Kakizaki, Rio; Sakamoto, Sumika; Noda, Yasuko; Yamada, Hisao; Kitada, Masaaki
Abstract : Cytoplasmic polyadenylation element binding protein 1 (CPEB1) regulates the translation of numerous mRNAs. We previously showed that AU‐rich binding factor 1 (AUF1) regulates Cpeb1 expression through the 3' untranslated region (3'UTR). To investigate the molecular basis of the regulatory potential of the Cpeb1 3'UTR, here we performed reporter analyses that examined expression levels of Gfp reporter mRNA containing the Cpeb1 3'UTR. Our findings indicate that CPEB1 represses the translation of Cpeb1 mRNA and that miR‐145a‐5p and let‐7b‐5p are involved in the reduction in Cpeb1 expression in the absence of AUF1. These results suggest that Cpeb1 expression is post‐transcriptionally regulated by AUF1, CPEB1, and microRNAs. Abstract : We have previously shown that loss of interaction between AREs in the Cpeb1 3'UTR and AUF1, an mRNA decay factor, increased Cpeb1 mRNA levels but reduced the protein levels (Oe S. et al . 2021, Biochem Biophys Res Commun 534, 491‐497). In this study, we revealed that Cpeb1 expression is post‐transcriptionally regulated by multiple inhibitory machineries that are regulated by AUF1, CPEB1, and microRNAs.